Microscopic Evaluation of Cast Iron with Flake Shape of Graphite - Kováčiková, Petra; Dubec, Andrej; Vavro, Ján (Manufacturing Technology Journal, 2019)
This paper deals with investigation of vibration damping properties of grey iron by means of modal analysis in SolidWorks software environment. Modal analysis is accompanied by material study of metal matrix and graphite particles evaluation. Grey iron is one of the most used cast materials, in relation to good damping properties and high pressure strength. To obtain the required mechanical properties it is necessary that the graphitic particles be evenly distributed in the metal matrix and had the optimum size and shape. Flake shape of graphite decrease tensile strength of grey iron, but a suitable method of inoculation, it can cause an increase of tensile strength up to 350 MPa. Flake shape of graphite particles increases the thermal conductivity. Grey iron is material with used in the manufacture of heavy machine stands, pump bodies and low-stressed sliding bearings in the context of with its characteristic material properties.
Keywords: Cast iron; Flake graphite; Microstructure; Finite element methods